Permian alkaline granites in the Erenhot–Hegenshan belt, northern Inner Mongolia, China: Model of generation, time of emplacement and regional tectonic significance. (1st January 2015) - Tong, Ying; Jahn, Bor-ming; Wang, Tao; Hong, Da-wei; Smith, Eugene I.; Sun, Min; Gao, Jian-feng; Yang, Qi-di; Huang, Wei
Abstract: The Central Asian Orogenic Belt (CAOB) is known to be the Earth's largest Phanerozoic accretionary orogenic belt. Its southern margin, particularly in the southern Mongolia and Inner Mongolia (SMIM), shows an extensive distribution of alkaline granites. Study of these granites could shed light on long-debated hypotheses on the late Paleozoic tectonic evolution of this region. In this work, we performed a detailed zircon age determination and whole rock geochemical analysis on alkaline granites from four granitic plutons in northern Inner Mongolia (Hongol, Saiyinwusu, Baolag, and Baiyinwula). U–Pb zircon dating yielded early Permian ages (ca. 280 Ma) for the four plutons. Whole-rock geochemical analyses show chemical characteristics typical of alkaline granites. Coeval alkaline granites from southern Mongolia to northern Inner Mongolia constitute a gigantic (∼900 km) Permian (292–275 Ma) alkaline granite belt in the southern CAOB. Furthermore, these alkaline granites have whole-rock ε Nd ( t ) varying between +3.6 and +6.4 and zircon ε Hf ( t ) from +4.9 to +20.3. The geochemical and Nd–Hf isotopic signatures suggest derivation by partial melting of a protolith assemblage dominated by metasomatised mantle, and followed by fractional crystallization in a post-collisional extensional environment.